(untitled) (International Journal of Engineering and Computer Science, 2017)
One of the biggest challenges for mankind in the century of 21 is use of alternative sources for nonrenewable, limited fossil fuels that tremendously contribute on the problem of global warming. In this challenge, solar energy production is rapidly becoming a vital source of renewable energy being developed as an alternative to traditional sources of power. For improving the efficiency of solar devices various approaches was intended but nanotechnology, a combination of chemistry and engineering, is viewed as new candidate for clean energy applications. Nanotechnology will bring significant benefits to the energy sector, especially to energy storage and solar energy. Improved materials efficiency and reduced manufacturing costs are just two of the real economic benefits that nanotechnology already brings these fields. This paper reviews recent advances on development of nanotechnology in the solar energy devices. Special emphases are given to solar cells based on nanostructure and nanodevices.